Emerging Socio-Technical Networks of Innovation in Architectural Practice. (March 2013) - Kocaturk, Tuba
This article reports on the initial analyses and findings of on-going research project which investigates the socio-technical transformation of Architectural practice due to technology adoption. A conceptual framework is developed as a tool to identify, analyse, and characterize the different socio-technical networks in current practice, and the ways in which these networks are being developed and coordinated. Highly technology-mediated and interdisciplinary architectural/engineering practices have been monitored and studied in their real-life project contexts. Through comparative case analyses, a conceptual framework has been developed and used to represent and analyse emerging socio-technical networks and the ways in which these networks facilitate innovation. In this context, new modes/practices of innovations are identified through the diverse and dynamic relationships emerging between architects, digital tools/systems, the design artefact, and the various multi-disciplinary knowledge/actors in a socio-technical setting.